PERAN GURU DALAM PEMBENTUKAN KEPRIBADIAN SISWA - Ainun Nabila; Muhammad Samsuri; Iffah Mukhlisah (Institut Islam Mamba'ul 'Ulum Surakarta, 2023)
This study aims to determine the role of the teacher's character in the formation of the personality of junior high school students. The approach used in this research is a qualitative approach with a descriptive method. The subject of this research is Muhammadiyah 1 Sukoharjo Junior High School. The data collection techniques used were interviews, observation, and documentation studies. The primary data sources for the study were 3 teachers at Muhammadiyah 1 Sukoharjo Junior High School, and secondary data in the form of documentation. Data analysis used is data reduction, data presentation, and verification. The results of this study indicate that teachers hold guidance programs in religious activities, procure guidance books, then supervise, assess and evaluate as well as cooperate with parents. The last role of the teacher is the teacher as a leader, namely the teacher being a good role model for students and acting according to applicable norms.